Prospects of studying tribo- and electrochemical effects in snow cover of Antarctica - E. Yu. Tkachenko; S. P. Olshtynsky (Ukrainian Antarctic Journal, 2010)
We create laboratory equipment with aim to confirm the proposed hypothesis and to study the chemical and physical impacts of snow triboelectrification under the wind. Such equipment may become a prototype of industrial units for environmentally safe destruction of dangerous organic substances.